The effect of sulphur dioxide on probiotic and pathogenic bacteria of the human gastrointestinal tract - Shah, Usman Ali (2020)
The major objective of the present research work was to determine the effect of sulphur dioxide (SO2) on probiotic bacterial strains (Lactobacillus acidophilus KI, Lactobacillus rhamnosus R11, Lactobacillus plantarum , Bifidobacterium animalis Bo, and Bifidobacterium animalis Bb12) and pathogenic bacterial strains that could affect gastrointestinal system (GIT) (Listeria monocytogenes, Escherichia coli, Salmonella enteritidis, and Bacillus cereus) using an in vitro simulation model. In a first step, growth curves were performed for both probiotic and pathogenic strains in culture media supplemented with SO2 at 1000 mg/L and 500 mg/L and the optical densities were registered. It was observed that SO2 at 500 mg/L did not cause significant reduction of any of the microorganism, however, the higher concentration of SO2 (1000 mg/L) exhibited an inhibitory effect on B. animalis Bo. As for the pathogenic strains, only L. monocytogenes and in a less extent E. coli were inhibited when treated with SO2 (1000 mg/L). The evaluation of the effect of SO2 at 1000 mg/L on the viability of B. animalis Bo was further performed and a reduction of 1 log was registered. When exposed to GIT conditions, the SO2 showed to somewhat protect pathogenic strains from stomach conditions. At intestinal simulated conditions an inactivation effect of SO2 at 1000 mg/L on B. animalis Bo was observed (1.9 log reduction). The other probiotic strains did not suffer a significant inactivation effect, in fact, it seems that are protected by the presence of SO2. Along the GIT simulation, the concentration of SO2 did not change significantly, but according with the zeta potential the chemical form of the compound changes from sulphite (SO32-) to bisulphites (HSO3-) and then to sulphur dioxide (SO2), with the pH modulation from gastric to intestine conditions. Also, the metabolism of B. animalis Bo in the presence of SO2 (1000 mg/L) is highly affected especially the glucose consumption. But no changes were observed in the production of organic acids such as acetic, and propionic acids, but lactic and citric acids were highly affected, succinic acid was somehow inhibited, but no production of butyric acid was observed. As a conclusion, in general, SO2 is not harmful for gut microbiota if ingested with food and it’s a safe compound to use for food preservation. Nevertheless, if ingested jointly with contaminant bacteria or when finding these bacteria at gut, this compound don´t perform any antimicrobial effect.